Uji Akurasi Pengukuran Arah Kiblat Masjid dan Makam di Kelurahan Malino Kecamatan Tinggimoncong Kabupaten Gowa - Nuraeni; Latuconsina, Mahyuddin; Khalik, Subehan (HISABUNA: Jurnal Ilmu Falak, 2024)
Determining the Qibla direction for mosques and tombs in Malino Village, Tinggimoncong District, Gowa Regency still uses a simple method due to the lack of public knowledge regarding the urgency of determining the Qibla direction even outside the tolerance limit. This research is a field research that applies qualitative research methods, using syar'i, astronomy and sociology approaches. The data sources used are primary and secondary data. The purpose of this study is to understand the method of determining the Qibla direction of mosques and tombs in the Malino Village, Tinggimoncong District, Gowa Regency, therefore it is necessary to re-measure to find out the actual Qibla direction by using several to determine the accuracy of Qibla direction. In this study there are five mosques and two graves which are used as examples regarding the position of the Qibla direction. The results showed that the accuracy of the Qibla direction at mosques and tombs in the Malino Village, Tinggimoncong District, Gowa Regency was still inaccurate. Therefore, it is necessary for the government to socialize and pay attention to the Qibla direction in mosques and graves.